Implementation of the Transmitting Functionality on the TIGER-3 FPGA-based Transceiver Platform - Wolpe, Luka (Department of Electrical Engineering, 2023)
High Frequency (HF) radio waves (3-30 MHz) are commonly used in long-range communication applications or in radars that require long-range detection capabilities. This is due to the refraction of HF radio waves, where the transmitted wave bends back towards to the Earth. HF radio waves can therefore be used to detect ships that are located over the horizon or to monitor the sea states over vast oceanic regions. Additionally, the refraction of HF radio waves can be exploited to meet the perpendicularity requirement of the radio wave with the Earth's magnetic _eld lines in the high-latitude polar regions [1]. The reflections received from the ionosphere have proved to be paramount in the efforts of the scientific community to develop a better understanding of solar weather, which has numerous impacts on everyday life on Earth. Due to the ever-advancing digital hardware, transceivers that make use of HF frequencies are now relatively straightforward to implement. Furthermore, the ever-increasing speed at which digital systems can sample and process information has allowed for the generation of HF frequencies without the need for analogue up-converters. Digital systems have moved a significant portion of the transceiver functionality into the digital domain, thereby improving the sensitivity, signal to noise ratio, size, and design simplicity of the system. The SuperDARN is a collaborative network of HF radars that monitor solar weather conditions via the ionosphere in the polar regions. Since it's inception in the 1980s, the number of radars in the network has increased to 36. The South African National Space Agency (SANSA) currently oversees a digital radar platform, called the TIGER-3, at the 4th South African National Arctic Expedition (SANAE IV) base in Antarctica. The TIGER-3 transceiver is built around a Virtex-5 FPGA that is connected to various peripherals such as ADCs, DACs, and digital step attenuators that make it perfectly suited to a wide variety of HF radar applications. Currently, the mode of operation of the TIGER-3 platform is limited, as South African National Space Agency (SANSA) does not have access to the source code. Previous work [2] has detailed the design and implementation of the listening mode of operation on the TIGER-3 transceiver. This work details the design and implementation of SuperDARN transmitting functionality, as well as additional functionality that may be required in other HF radar applications. Modules were developed in Verilog to facilitate the generation of SuperDARN pulse sequences, window functions, and a receive client for the Ethernet communication link was implemented. Additionally, modulation techniques, such as Linear Frequency Modulation (LFM) and phase-shift keying, were implemented. Furthermore, a Graphical User Interface (GUI) was developed to easily change various performance parameters of the radar on the fly. The transmitting functionality developed in this work can then be integrated with listening mode functionality developed in previous work [2]. This would create a complete base implementation of the TIGER-3 transceiver platform, which can be built on in future work to perform both SuperDARN and secondary application tasks.